Hungarian Monitoring, 15 January 1990 . [Magyar rádiófigyelő], 1990. január 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Genscher's visit to Romania - Talks begin in Czechoslovakia concerning Soviet troop withdrawals - GDR roundtable talks: siege of state security HQ - Swiss investigations into Ceauşescu bank accounts - USSR: situation between Armenia and Azerbaijan Domestic Affairs: - Luxembourg's Foreign Minister in talks in Budapest - Romanian-Hungarian cultural relations - The Bokor affair - Dunagate scandal - Hungarian Democratic Forum (MDF) demonstration against price increases and re-privatization Economy: - Japanese premier discusses economic questions in Budapest Külpolitika: - Genscher romániai látogatása - Csehszlovákiában megbeszélések kezdődtek a szovjet csapatok kivonásáról - Az NDK kerekasztal tárgyalások; az államvédelmi központ ostroma - Svájci nyomozás Ceauşescu-bankszámlák ügyében - SZU: az örmény és azerbajdzsáni helyzet Belpolitika: - A luxemburgi külügyminiszter budapesti tárgyalásai - Román-magyar kulturális kapcsolatok - Bokor-ügy - Dunagate-botrány - MDF tüntetés áremelés és reprivatizáció ellen Gazdaság: - A japán kormányfő gazdasági kérdésekről tárgyal Budapesten